Family profile of children with ASD assisted at an Interdisciplinary Equine Therapy Center in the city of Santarém in the State of Pará (Research, Society and Development, 2022)
Objective: This study aimed to analyze the family profile of patients with ASD assisted by Centro Interdisciplinar de Equoterapia Santarém (CIEQ/STM), in order to enable better care and approaches to be passed on to these families and/or guardians. Methodology: This is a quantitative, descriptive and cross-sectional study, with an epidemiological basis. The present research took place in the municipality of Santarém, Pará. This study checked data obtained from the 23 medical records of individuals diagnosed with ASD, from September 2015 to January 2020, considering the following inclusion criteria: medical records of individuals treated at the Interdisciplinary Center for Riding Therapy in the city of Santarém during the period from 2015 to 2020. Results: Among the parents eligible for the survey, it was found that 69.6% of the patients had a father registered in the file, and among these, an average age of 42 years was found, maternal age on average 38.2 years with a standard deviation of 8 years. Economic profile, it is observed that the majority (n=8, representing 34.7%) of the families account for an income of 1 to 3 minimum wages. Conclusion: The greater amount of positive classification in the level of satisfaction of family relationships can be explained not only by the result of the work and research of the professionals who accompany these individuals and guide them with facilitation of understanding and understanding the reality in which families find themselves, but also because of the quality of life offered to the ASD patient they live with.